Intraduktale papillär-muzinöse Neoplasie des Seitengangs: pro Resektion - Kaiser, Jörg; Büchler, Markus W.; Hackert, Thilo (Der Chirurg, 2017)
Due to increasing precision of modern imaging modalities, intraductal papillary mucinous neoplasms (IPMN) of the pancreas are found with increasing prevalence. Despite their malignant potential IPMN are often kept under surveillance and are not immediately resected. The 2012 International Consensus Guidelines of Fukuoka have been widely accepted for the management of IPMN. They recommend surgical resection for branch duct IPMN with “high risk stigmata”, while branch duct IPMN with “worrisome features” should undergo observation without immediate resection. Consequently, patients with asymptomatic branch duct IPMN and a presumed low malignant potential mostly undergo primary surveillance to avoid surgery-related morbidity and mortality following pancreatic resection; however, with respect to the cumulative risk of malignant transformation over time, surgical resection might also be indicated for patients with branch duct IPMN with “worrisome features”. This article discusses the indications for surgery and different options of resection of branch duct IPMN.